Text Translation Method by Considering Information Distribution in the Form of Theme-Rheme Relation - Zulia Karini (University of Muhammadiyah Purwokerto, 2018)
This study will analyze the translation of sentences in the text by giving consideration to the distribution of information presented in the form of Theme-Rheme relation. First we will identify Themes - Rheme in the sentences in the text and will analyze the results of the translation. The theme is information that is priori-tized in a sentence usually placed in the beginning of sentence, and Rheme is the proposed information. There are three types of Themes, namely Topical Theme, Interpersonal Theme, and Textual Theme. The object of discussion here is the Topical Themes, which are Themes relating to how the subject matter discussed in the clause or sentence is laid out. Topical themes are divided into two types: Marked Topical Theme and Un-marked Topical Theme. The analysis of Topical Themes are taken from a bilingual children's book entitled Sangkuriang from the publisher Nexx Media Inc., Bandung. Sangkuriang is one of the popular Indonesian folklore that tells of a very beautiful mother whose admirer is his own son. The text to be analyzed is part of the text that tells about the birth of Dayang Sumbi, the mother of Sangkuriang. From the result of the whole analysis, the source text consists of 10 Marked Topical Theme and Top 10 Unmarked Topical Theme. There are some Topical theme changes from the source text to the target text: a sentence with an Unmarked Topical Theme is translated into a sentence with a Marked Topical Theme, and vice versa. Based on the analysis of Topical Themes on the Source Text and Target Text it can be concluded that there are some sentences that have shifted Topical Themes. There have been some changes in information due to the shift in this Topical Theme, so it can be said that this translation is not good. At the end of the analysis is given an edit on the target text. The edit of this translation does not change the Topical Theme from the Source Text, so the sub-ject matter in each sentence of the Target text is the same as the subject matter in each sentence of the Source Text.